Give it a rest: a systematic review with Bayesian meta-analysis on the effect of inter-set rest interval duration on muscle hypertrophy - Singer, Alec; Wolf, Milo; Generoso, Leonardo; Arias, Elizabeth; Delcastillo, Kenneth; Echevarria, Edwin; Martinez, Amaris; Androulakis Korakakis, Patroklos; Refalo, Martin C.; Swinton, Paul A.; Schoenfeld, Brad J. (Frontiers in Sports and Active Living, 2024)
We systematically searched the literature for studies with a randomized design that compared different inter-set rest interval durations for estimates of pre-/post-study changes in lean/muscle mass in healthy adults while controlling all other training variables. Bayesian meta-analyses on non-controlled effect sizes using hierarchical models of all 19 measurements (thigh: 10; arm: 6; whole body: 3) from 9 studies meeting inclusion criteria analyses showed substantial overlap of standardized mean differences across the different inter-set rest periods [binary: short: 0.48 (95%CrI: 0.19–0.81), longer: 0.56 (95%CrI: 0.24–0.86); Four categories: short: 0.47 (95%CrI: 0.19–0.80), intermediate: 0.65 (95%CrI: 0.18–1.1), long: 0.55 (95%CrI: 0.15–0.90), very long: 0.50 (95%CrI: 0.14–0.89)], with substantial heterogeneity in results. Univariate and multivariate pairwise meta-analyses of controlled binary (short vs. longer) effect sizes showed similar results for the arm and thigh with central estimates tending to favor longer rest periods [arm: 0.13 (95%CrI: −0.27 to 0.51); thigh: 0.17 (95%CrI: −0.13 to 0.43)]. In contrast, central estimates closer to zero but marginally favoring shorter rest periods were estimated for the whole body [whole body: −0.08 (95%CrI: −0.45 to 0.29)]. Subanalysis of set end-point data indicated that training to failure or stopping short of failure did not meaningfully influence the interaction between rest interval duration and muscle hypertrophy. In conclusion, results suggest a small hypertrophic benefit to employing inter-set rest interval durations >60 s, perhaps mediated by reductions in volume load. However, our analysis did not detect appreciable differences in hypertrophy when resting >90 s between sets, consistent with evidence that detrimental effects on volume load tend to plateau beyond this time-frame. Systematic Review Registration: OSF, https://doi.org/10.17605/OSF.IO/YWEVC.